2008
DOI: 10.1038/jid.2008.157
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of uPAR Is Associated with the Progression of Dermal Fibrosis

Abstract: The fibrinolytic system is considered to play an important role in the degradation of extracellular matrices (ECM). However, the detailed mechanism regarding how this system affects fibrosis remains unclear. Urokinase-type plasminogen activator receptor (uPAR) not only functions as a proteinase receptor but also plays a role in cellular adhesion, differentiation, proliferation, and migration through intracellular signaling. To investigate the effect of uPAR on dermal fibrosis, the skin of wild-type mice was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
(25 reference statements)
2
45
0
Order By: Relevance
“…␣2AP rapidly inactivates plasmin, resulting in the formation of a stable inactive complex, plasmin-␣2AP (2). Apart from the removal of fibrin, the fibrinolytic system also plays a pivotal role in such phenomena as embryogenesis, proliferation, migration, wound healing, fibrosis, and tumorigenesis (3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…␣2AP rapidly inactivates plasmin, resulting in the formation of a stable inactive complex, plasmin-␣2AP (2). Apart from the removal of fibrin, the fibrinolytic system also plays a pivotal role in such phenomena as embryogenesis, proliferation, migration, wound healing, fibrosis, and tumorigenesis (3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In light of convincing evidence from in vitro studies, the analysis of two independently generated uPAR-deficient mouse lines has, surprisingly, demonstrated that fibrinolysis is not generally affected by uPAR loss and that spontaneous phenotypes are virtually absent in these mice [13,14]. However, dermal fibrosis [15] and nervous system defects [16] have been described in unchallenged uPAR-deficient mice. The plasminogen activation system has been associated with cancer progression.…”
Section: Introductionmentioning
confidence: 95%
“…Relationship between SSc and uPAR was studied in dermal fibroblasts and endothelial cells obtained from SSc skin lesions, where a decrease in uPAR was detected compared to healthy control cells [57]. Recent studies have demonstrated the effect of inactivation of uPA/uPAR on transdifferentiation of fibroblasts into myofibroblasts and structural and functional changes in vasculature in SSc [58,59]. uPAR−/− mice mimic fibrotic and vascular manifestations of SSc, which supports a significant role of the uPA/ uPAR in the pathogenesis of SSc.…”
Section: Upar−/− Micementioning
confidence: 99%